2015
DOI: 10.1111/jsm.12792
|View full text |Cite
|
Sign up to set email alerts
|

Newly Diagnosed Erectile Dysfunction and Risk of Depression: A Population-Based 5-year Follow-Up Study in Taiwan

Abstract: Introduction Depression might increase the risk of erectile dysfunction (ED), and ED might further exacerbate depression. The causal relationship between these two diseases remains controversial. In addition, limited evidence is available regarding the age-dependent and time-dependent effects on the association of depression and ED. Aim We investigated the hypothesis that ED increases the risk of depression by using a nationw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Even though females are more likely to suffer from depression 31 and males are less frequently affected by SSc, we were still surprised that there were no males present in the subgroup of patients with depressive symptoms. Particularly knowing that male patients with SSc often suffer from erectile dysfunction, 32 which in turn can be responsible for a higher likelihood of developing depression, 33 this result came as a surprise. It is possible that the low case number of male patients (n=12) in our study might be responsible for this result and that higher case numbers might lead to a different result.…”
Section: Discussionmentioning
confidence: 99%
“…Even though females are more likely to suffer from depression 31 and males are less frequently affected by SSc, we were still surprised that there were no males present in the subgroup of patients with depressive symptoms. Particularly knowing that male patients with SSc often suffer from erectile dysfunction, 32 which in turn can be responsible for a higher likelihood of developing depression, 33 this result came as a surprise. It is possible that the low case number of male patients (n=12) in our study might be responsible for this result and that higher case numbers might lead to a different result.…”
Section: Discussionmentioning
confidence: 99%
“… 29 The ED may increase the risk of developing depression by 8.7–43.1% as compared to those who do not have ED. 29 , 30 On the other hand, there are some antidepressant drugs belonging to the selective serotonin reuptake inhibitor (SSRI) class which are known to increase the risk of developing ED. One of these drugs is paroxetine.…”
Section: Introductionmentioning
confidence: 99%
“…In a longitudinal study of Asian men with ED, Chou et al reported a high risk of developing depression, particularly within 1 year of ED diagnosis. Chou et al also reported that patients with ED had a 2.24-fold higher HR for developing depression compared to controls without ED [ 31 ]. Diem et al reported that depression symptoms in elderly males are associated with an approximately 1.8-fold increase in the annualised rate of bone loss in the hip, femoral neck, and trochanter bones [ 33 ].…”
Section: Discussionmentioning
confidence: 99%